Studi Kelayakan Teknis Dan Finansial Proyek Pembangunan Hotel X Pekanbaru - Shesilya Febita; Hendra Taufik (Jurnal Online Mahasiswa (JOM) Bidang Teknik dan Sains, 2016)
Rapid development of hotel constructions in Pekanbaru due to economic growth make national and international investors eager to transform Pekanbaru City into business place. Investation in lodging sector is very risky because the funds needed as initial investment is enormous. Therefore, appropriate technical and financial feasibility studies are necessary. The technical feasibility study includes the analysis of spaced required for parking slots, whereas the financial feasibility study includes the analysis of net present value, benefit cost ratio, internal rate of return, payback period, and sensitivity analysis. The analysis result shows that the available parking slot is 188 SRP, which is smaller than the standard required parking slot stated by Dirjen Perhubungan Darat (279 SRP). This indicates that the available parking slots full fill about 67% of the standard parking requirement. Hotel investation Rp 265.276.637.520,55 with NPV Rp 55.955.191.071,46, BCR is 1,11, IRR 19,82% is bigger than return flow of 13,50% and PBP for 10 years and 7 months (project plan life is 50 years). In summary, the investation project of X Hotel construction is financially feasible if the minimum hotel occupancy of 46,90%. However, the investation project is not feasible for the technical aspect.Keywords : Technical Analysis, Financial Analysis, Sensitivity Analysis, X Hotel, Occupancy Hotel.